1973
DOI: 10.1159/000180224
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Plane Dipslide Quantitation of Bacteriuria

Abstract: The reliability of the Uricult dipslide in the quantitative estimation of bacteriuria has been tested on 2,596 urines from out-patients and in-patients of various types. The dipslide results at 15–20°C and at 37°C correspond almost exactly with pour-plate controls in 340 urines. False-positive and false-negative results were negligible. The dipslide results correspond well, but not so completely, with those from 1,000 urines tested by the less accurate standard-loop technique. Dipping by ward sister… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Quantitative urine culture was performed using a dip-slide method (Urotube, Becton Dickinson) and urine was also streaked on MacConkey agar. This dip-slide method has been shown to correlate well with conventional methods [21,22]. After incubation at 37°C for 24 h, the microorganisms were identified by standard biochemical tests.…”
Section: Methodsmentioning
confidence: 92%
“…Quantitative urine culture was performed using a dip-slide method (Urotube, Becton Dickinson) and urine was also streaked on MacConkey agar. This dip-slide method has been shown to correlate well with conventional methods [21,22]. After incubation at 37°C for 24 h, the microorganisms were identified by standard biochemical tests.…”
Section: Methodsmentioning
confidence: 92%
“…In the present trial a more detailed search for infection has been made in an attempt to obtain an accurate incidence of post-instrumentation infection, with 4 serial urine samples being examined over a 2-week period after the cystoscopy (see Patients and Methods). Since 3 of the 4 post-cystoscopy urine samples were to be given after the patient's discharge from hospital, dip slides were used as a screening test since it has been shown that they are accurate in detecting urinary tract infections (Guttman and Naylor, 1967;McAllister et al, 1973). This technique was backed up by MSU analysis where infection was suspected from the dip slide results.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial growth occurring on the dip slides was described as confluent, semi-confluent or moderate. A confluent or semi-confluent growth of bacteria on the dip slides has been found to correlate with significant bacteriuria (Guttman and Naylor, 1967;McAllister et al, 1973).…”
mentioning
confidence: 99%
“…This dip–slide method has been shown to correlate well with conventional methods [1, 2]. After incubation at 37°C for 24 h the microorganisms were identified by standard biochemical tests.…”
Section: Methodsmentioning
confidence: 99%